TO PROBLEMS OF PUBLIC ADMINISTRATION - A. M. Gogolev (Финансы: теория и практика)
It is generally believed that the subject of any investigation should be a problem the solution of which removes an apparent or actual contradiction. But the very idea of social management as a mechanism for conflict cooperation involves solid contradictions and problems. Every solution generates new problems. With this approach, the subject of the public administration theory is scientific substantiation of the process of achieving the optimal government control by improving the organization of such activities. The author notes that, in addition to philosophical and ideological principles the methodology of administrative law includes general and special research methods that apply to other law sciences. Moreover, each science is to shape their own methodological basis relying on the general theory of knowledge. With regard for specific targets and objects of research, different sciences have a common goal - to provide society with new evidence-based structured knowledge. It is concluded that the integrated use of different methods and approaches contributes to the establishment and generalization of specific features of the legal institution and solving problems of its legal regulation at the federal and regional levels.